POLA BIMBINGAN BELAJAR SISWA TUNARUNGU SAAT PANDEMI COVID-19 DI SLB NEGERI GUNUNGSARI - Khairi, Alfin Miftahul; Ningrum, Ranty Purwita (UIN Sunan Kalijaga Yogyakarta, 2022)
The purpose of this study was to determine the pattern of tutoring for deaf students during the Covid-19 pandemic at SLB Negeri Gunungsari Baureno Bojonegoro. The researcher uses a qualitative method with a case study approach, the technique of determining the subject is through purposive sampling. Data collection techniques through interviews, observation, and documentation. The results of this study indicate that the pattern of tutoring provided by the teacher to deaf students at SLB Negeri Gunungsari Baureno is in the form of intensive communication, additional subject matter, direction, cooperation with parents, and additional assignments. Tutoring is carried out online and home visit are provided according to the needs of deaf students. Learning assistance through tutoring services was responded to by both the parents and the deaf students. In addition, deaf students show good learning development. Keywords: covid-19, tutoring, deaf student.